2019
DOI: 10.3390/antibiotics9010012
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Autoimmune Thyroid Diseases: The Role of Virulent Strains

Abstract: Aim: To verify a possible association between overall H. pylori and CagA+ H. pylori infection and autoimmune thyroid diseases (AITDs). Methods: Consecutive patients with AITDs admitted to one single centre of Endocrinology during one solar year were examined. The diagnoses were Hashimoto thyroiditis (HT) in 76, Graves’ Disease (GD) in 39, and aspecific thyroiditis (AT) in 44 patients. Controls were 136 individuals without AITDs. Median values of fT3, fT4, anti-thyreoglobulin (Tg) antibodies, IL-1β, IL-6, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 38 publications
(41 reference statements)
2
30
0
Order By: Relevance
“…H. pylori infection is also involved in the development of AITD (41). Specifically, TgAb was significantly more prevalent in infected AITD patients than in those without infections (42). It has been found that Tg shares putative conserved structure with H. pylori proteins, while TPO only exhibits a partial linear homology and thus has less potentials for epitope mimics (42).…”
Section: Referencesmentioning
confidence: 99%
“…H. pylori infection is also involved in the development of AITD (41). Specifically, TgAb was significantly more prevalent in infected AITD patients than in those without infections (42). It has been found that Tg shares putative conserved structure with H. pylori proteins, while TPO only exhibits a partial linear homology and thus has less potentials for epitope mimics (42).…”
Section: Referencesmentioning
confidence: 99%
“…Previous studies on the association between H. pylori infection and thyroid diseases have mostly focused on thyroid autoimmunity, and the correlation between H. pylori infection and thyroid autoimmune diseases, such as Graves disease and Hashimoto thyroiditis, has been reported (Benvenga and Guarneri, 2016;Kohling et al, 2017;Figura et al, 2019). Shen et al (2013) found that H. pylori infection was positively associated with the risk of TN types.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed many interrelationships in embryology, phylogeny and function between the thyroid and the gastrointestinal tract through the adulthood (Miller et al, 1978). The molecular mimicry mechanisms also provide a reasonable explanation for the role of intestinal flora in triggering autoimmune diseases (Benvenga and Guarneri, 2016;Sousa Mde et al, 2016;Figura et al, 2019). Changes in the composition of gut microbiota have been confirmed to be related to the development of several autoimmune diseases, including RA (Yeoh et al, 2013), SLE (Lopez et al, 2016), MS (Shamriz et al, 2016) and Behcet's disease (Consolandi et al, 2015).…”
Section: Discussionmentioning
confidence: 96%